2021
DOI: 10.3390/f12060673
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Changes in Vegetation Cover and Its Influencing Factors in the Loess Plateau of China Based on the Geographically Weighted Regression Model

Abstract: Vegetation plays a key role in ecosystem regulation and influences our capacity for sustainable development. Global vegetation cover has changed dramatically over the past decades in response to both natural and anthropogenic factors; therefore, it is necessary to analyze the spatiotemporal changes in vegetation cover and its influencing factors. Moreover, ecological engineering projects, such as the “Grain for Green” project implemented in 1999, have been introduced to improve the ecological environment by en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…GDP per capita was found to be positively correlated with water yield. This discovery is consistent with the research results of (Yang et al 2021, Sun et al 2017, Li et al 2018. The increased water yield with GDB per capita and the growth rate of construction land have a firm consistency, with correlation coefficients of 0.89 (p < 0.05) and 0.93 (p < 0.05), respectively.…”
Section: Water Yield Change's Driving Factorssupporting
confidence: 91%
See 1 more Smart Citation
“…GDP per capita was found to be positively correlated with water yield. This discovery is consistent with the research results of (Yang et al 2021, Sun et al 2017, Li et al 2018. The increased water yield with GDB per capita and the growth rate of construction land have a firm consistency, with correlation coefficients of 0.89 (p < 0.05) and 0.93 (p < 0.05), respectively.…”
Section: Water Yield Change's Driving Factorssupporting
confidence: 91%
“…While the study of Yang et al (2021) shows that the correlation of GDP per capita to vegetation cover (and the result correlation with water yield) shows no clear pattern, it can be positively or negatively correlated. Research in the Loess Plateau, China, found that the relationship of GDP per capita to vegetation change (individually effect) was positive.…”
Section: Water Yield Change's Driving Factorsmentioning
confidence: 90%
“…In this study, a Geographically Weighted Regression (GWR) model was used to reveal the interpretability of land use type changes on vegetation cover restoration, considering spatial autocorrelation and spatial heterogeneity 37 . The formula is as follows:…”
Section: Geographically Weighted Regression Modelmentioning
confidence: 99%
“…The NDVI can be used to characterize the degree of vegetation cover and has been widely applied in different fields of study [49][50][51][52], so it can be used to represent the vegetation cover in Chongqing. In our study vegetation cover is considered as the value to monitor the degree of vegetation growth.…”
Section: Research Frameworkmentioning
confidence: 99%